2006
DOI: 10.1093/eurheartj/ehl285
|View full text |Cite
|
Sign up to set email alerts
|

Coronary plaque composition of culprit/target lesions according to the clinical presentation: a virtual histology intravascular ultrasound analysis

Abstract: Plaque composition obtained by VH-IVUS shows less necrotic core and more fibrous tissue in ACS compared to SAP lesions, which is in contradiction with previously published histopathologic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 35 publications
(55 reference statements)
1
29
0
Order By: Relevance
“…43 On the other hand, controversial results also exist on the relationship between the virtual histology findings and clinical presentations (less necrotic core and more fibrous tissue in acute coronary syndromes). 44 Current technical limitations include limited spatial resolution (100 to 250 m), no classifications for thrombus, blood, or intimal hyperplasia, and potential errors due to poor ultrasound penetration through extensive calcification. Among several multicenter studies initiated worldwide, PROSPECT (Providing Regional Observations to Study Predictors of Events in the Coronary Tree) is one of the largest natural history trials; it used 3-vessel imaging with Virtual Histology and IVUS palpography (see below) in 700 acute coronary syndrome patients.…”
Section: Ultrasound-based Approachesmentioning
confidence: 99%
“…43 On the other hand, controversial results also exist on the relationship between the virtual histology findings and clinical presentations (less necrotic core and more fibrous tissue in acute coronary syndromes). 44 Current technical limitations include limited spatial resolution (100 to 250 m), no classifications for thrombus, blood, or intimal hyperplasia, and potential errors due to poor ultrasound penetration through extensive calcification. Among several multicenter studies initiated worldwide, PROSPECT (Providing Regional Observations to Study Predictors of Events in the Coronary Tree) is one of the largest natural history trials; it used 3-vessel imaging with Virtual Histology and IVUS palpography (see below) in 700 acute coronary syndrome patients.…”
Section: Ultrasound-based Approachesmentioning
confidence: 99%
“…21 According to VH-IVUS, the FF component is associated with development of acute coronary syndrome. 22 As shown in the TRUTH study, statins have the plaque-stabilizing effect of decreasing the FF component. 9 Kovarnik et al also reported the same results using dual lipid-lowering therapy with statin plus ezetimibe.…”
Section: Discussionmentioning
confidence: 90%
“…1) Pathological data also shows that high-risk plaques such as vulnerable TCFA have more NC volume than stable plaques. 25) Furthermore, a previous report by IVUS also reported that ACS patients showed a significantly higher ratio of NC plaque compared with SAP patients, and VH-IVUS-derived TCFA was more frequently observed in ACS patients compared with SAP patients. 26) In the present study, the ACS group had significantly more %NC and NC volume and less %Fibrous than the SAP group.…”
Section: Difference In Ivus and Vh-ivus Parameters Between Acsmentioning
confidence: 89%
“…However, VH-IVUS data concerning the relationship of NC to clinical presentation are still controversial. 25,27) In VH-IVUS studies, the presence of thrombi in ACS lesions may influence plaque composition because thrombi are not recognized as a different component but assigned to one of the four available components (usually fibrous or fibro-fatty by VH-IVUS).…”
Section: Difference In Ivus and Vh-ivus Parameters Between Acsmentioning
confidence: 99%